Crystal structure of (Z)-2-hydroxy-N′-(1-(o-tolyl)ethylidene)benzohydrazide, C16H16N2O2 - Liu Bin; Xu Xiaona; Zhu Zhoujing (Zeitschrift für Kristallographie - New Crystal Structures)
C16H16N2O2, orthorhombic, Pbca (no. 61), a = 12.5980(5) Å, b = 12.8535(4) Å, c = 17.5963(7) Å, V = 2849.34(18) Å3, Z = 8, Rgt(F) = 0.0464, wRref(F2) = 0.1396, T = 298 K.